Market Retribution Market Potential Analysis in Malang City - Mulyono; Survival (Optima Science, 2023)
The factors that determine the success of collecting market levies are the number of traders, the area of ​​kiosks, stalls and open grounds, rates and the collection performance (efficiency and effectiveness of collection) of market levies. Because more and more people are taking advantage of regional government services, regional revenues from levies are also increasing. This can be seen from the economic development of the Malang City area, therefore the presence of traders greatly influences the effectiveness of market levy receipts. The aim of the work on preparing this potential market levy analysis document is to: 1) Examine current market management patterns based on relevant regulations or policies. 2) Identify and study the pattern of determining levies or rents on markets based on market classification in order to measure more optimal levels of income. This type of research is policy research which aims to explore various information related to market service fees in order to provide recommendations for policy making for regional (market) asset management. The analysis technique in this research uses descriptive statistical analysis techniques. The research results show that optimization of sources of Regional Original Income (PAD), including market levies, needs to be carried out to improve the regional financial capacity of Malang City. What can be done immediately is to intensify existing regional income objects or sources, especially through the use of information technology.